SISTEM PENDUKUNG KEPUTUSAN UNTUK PENENTUAN JURUSAN KULIAH MENGGUNAKAN METODE NAIVE BAYES - Nur Utami Wahdaniati; Ria Rismayati; Ismarmiaty (Universitas Islam Negeri Mataram, 2024)
This research aims to develop a Decision Support System (SKS) to help MAN 1 Bima City students in determining college majors that match their interests, talents, and potential. In this system, the Naive Bayes method is used to process data and provide recommendations based on factors such as academic grades, interests, and career prospects. This system is designed to overcome the limitations of manual processes that are often subjective and inconsistent. The methodology used in this research is Sythe Systemevelopment Life Cycle (S(SDLC),hich includes the stages of needs analysis, design, implementation, and testing. The data used includes students' report cards from sesemesters and 2 of grade 12. The system is also designed to allow the management of information related to college majors by administrators and provide statistical reports on the results of rerecommendations.he test results show that this SPK is able to provide accurate major recommendations and ccordance with student profiles. Testing was conducted using the blacblack boxhod to ensure all system features function properly. The system also proved to be efficient and can save time and resources compared to the manual method. The conclusion of this research is that SPK with the Naive Bayes method can be an effective and efficient tool in the process of determining college majors. In addition, it is recommended to continue developing this system, such as by adding more comprehensive interest and talent test features, as well as increasing the accessibility of the system through mobile applications.